Systemic AA amyloidosis induced by liver cell adenoma. Issue 3 (March 1990) - Fievet, P; Sevestre, H; Boudjelal, M; Noel, L H; Kemeny, F; Franco, D; Delamarre, J; Capron, J P
Abstract : Systemic AA amyloidosis is a rare complication of benign tumours. This report describes a patient with hepatocellular adenoma associated with reactive AA amyloidosis. He had a nephrotic syndrome with deteriorating renal function and an increase of serum concentrations of acute phase proteins, mainly C-reactive protein. Resection of the tumour was followed by improvement in renal function and a marked decrease of the serum concentrations of acute phase proteins.